Particles in finite volumes and a toy model of decaying neutrons - Christian Käding (European Physical Journal C: Particles and Fields)
Abstract It is well-known that the momentum spectra of particles confined to finite spatial volumes deviate from the continuous spectra used for unconfined particles. In this article, we consider real scalar particles confined to finite volumes with periodic boundary conditions, such that the particles’ spectra are discrete. We directly compute the density matrices describing the decay processes $$φ → φ ^2$$ ϕ → φ 2 and $$φ → φ χ ν $$ ϕ → φ χ ν , and subsequently derive expressions for the decay probabilities both for confined and unconfined particles. The latter decay process is used as a rough toy model for a neutron decaying into a proton, an electron, and an anti-electron neutrino. We propose that finite volume effects can have an impact on the outcomes of experiments measuring the neutron lifetime. In addition, our findings at the toy model level suggest that taking into account possible initial correlations between neutrons and their daughter particles might be relevant as well.